IMPLIKASI YURIDIS TRANSFORMASI UNIT SYARIAH PERUSAHAAN ASURANSI/REASURANSI KE DALAM PERUSAHAAN ASURANSI/REASURANSI SYARIAH - Umam, Khotibul (Veritas et Justitia, 2021)
In this article the author examines the juridical implications of transforming Units of Insurance/Reinsurance Company into Sharia Insurance/Reinsurance Company. It peruses two different models, the pure model, and the acquisition model.  Both have its own strong and weak points. The pure models show its strongest point in being simpler about Sharia compliance.  Its weakness, however, is the requirement of priory obtaining permit in principle and business permits.  In contrast, the superiority of the acquisition model lies in its simplicity of licensing and conversion permits. Its disadvantage is in the complexity of contract conversion.  Regarding assets and liabilities, strict adherence to the Sharia principles, voluntarisms, and avoidance of the mixing of halal and haram, is a pre-requisite